Combination of QuEChERS and switchable-hydrophilicity solvent based liquid-liquid microextraction for the accurate determination of pyridalyl and metalaxyl pesticides at trace levels - Akbiyik, Hilal; Karakebap, Kubra; Girgin, Ayca; Turak, Fatma; Bakirdere, Sezgin (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2025)
Pesticides are extensively used in agriculture to protect crops and enhance the yield quality, but they may have adverse impacts to both human/ecological health. It is essential to develop reliable and sensitive methods for the determination of pesticides at ultra-trace levels. This research focused on the separation/extraction of the target pesticides, metalaxyl and pyridalyl, with the Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) technique coupled with Switchable-Hydrophilicity-Solvent based Liquid-Liquid Microextraction (SHS-LLME) method using gas chromatography-mass spectrometry (GC-MS). After obtaining the ions with m/z values based on the total ion chromatograms for both pesticides, the parameters affecting the extraction output, including pH and volume of the buffer solution, extraction solvent volume, concentration and volume of NaOH solution, mixing type and duration, and the composition of the extraction solvent were optimized. Following the optimization studies, limits of detection (LOD) and the limits of quantification (LOQ) were calculated as 0.012-0.039 mg kg(-1) and 0.0057-0.0190 mg kg(-1) for metalaxyl and pyridalyl, respectively. Under the optimum conditions, the SHS-LLME procedure was applied to both paprika powder/red pepper flake samples after applying QuEChERS method. Satisfactory results support the applicability of environmentally friendly and simple method for the quantification/enrichment of the selected analytes.
Keywords: Switchable hydrophilicity solvent; QuEChERS. gas chromatography-mass spectrometry; Metalaxyl; Pyridalyl; SAMPLE PREPARATION METHODS; SOLID-PHASE EXTRACTION; RESIDUE ANALYSIS; FRUITS; DISSIPATION; INSECTICIDE; Chemistry; Food Science & Technology